Pengujian Kepatuhan Pengendalian Internal Prosedur Kas pada Rumah Sakit Palang Biru Kutoarjo - Supriono; Reni Suci Wahyuni; Margaretta Nuke Tanjungsari (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This study aims to examine compliance with the internal control of cash receipts and disbursements implemented at Palang Biru Hospital. Cash receipt testing is carried out on cash receipt transactions from banks (payment points) and hospital cashiers. Meanwhile, testing cash expenditures on petty cash account expenditures. Testing compliance with internal control of cash procedures in this research uses the stop-or-go sampling method, with a constraint level (R) or confidence level of 95%. Results of internal control compliance testing for cash receipts on the attribute (1) documents with printed serial numbers, with the conclusion that this attribute is running well, (2) checking the cashier's deposit book with the conclusion that this attribute has not been met, (3) checking transaction reports and bank statements with conclusion has been fulfilled. Meanwhile, the results of testing compliance with internal control of cash disbursements on the attributes (1) document authorization, (2) completeness of documents, and (3) accuracy of accounting records concluded that the three attributes had not been met.